Characterization of the lactation curve of f1 Holstein-Zebu cows - Castillo-Gallegos, Epigmenio (Ecosistemas y Recursos Agropecuarios, 2018)
The objective was to nd a function to describe the lactation curve of grazing Holstein - Zebu cows (n=23) in tropical México. Twelve were based on the general nonlinear function A*Φ1(x)*Φ2(x): A, a positive scalar; Φ1 , a positive monotonically increasing function with asymptote Φ1 = 1; Φ2 , is a monotonically decreasing function with asymptote Φ2 = 0 and initial value of 1; and x is lactation time (days). For Φ1 , the Mitscherlitsch, Michaelis-Menten, generalized saturation kinetics, logistic, Gompertz and hyperbolic tangent equations were used, whilst for Φ2 , they were the exponential and inverse linear. A gamma function, the more used, and the addition of two logistic equations, the more biologically explicit, were also included. The smaller value of the Akaike information criterion corrected (AICc) indicated the latter was the one with the best t, so its use to study factors aecting the lactation curve is suggested.